Menilik Bentuk Komunikasi Antara Anak Dan Orang Tua - Muttaqin Zainul; Azmussya’ni Azmussya’ni (Tarbawi, 2021)
This type of research is a qualitative study of communication ethnography studies. Sources of data are informants and several documents related to the research topic. The data in this study are in the form of communication speech between parents and children in Kabar Village, Sakra District. The method of obtaining data uses the method of observation and unstructured interviews. Data analysis used three stages, namely data reduction, data analysis and drawing conclusions. At the results stage, three communication patterns were found: 1) Authoritarian Communication Patterns (Authotirrian), 2). Permissive Communication Patterns, and 3). Democratic Communication Pattern (Authoritative). Authors and permissive communication patterns are still dominant, while democratic communication patterns are still small. This cannot be separated from the insight, economy and parental education factors.